Observation on analgesic efficacy and adverse effects of intrathecal administration of bupivacaine versus bupivacaine-midazolam combination in lower limb surgeries in a tertiary care hospital - Mohsin, Md.; Kumari, Rekha (International Journal of Research in Medical Sciences, 2016)
Background: Postoperative pain relief can improve functionality, reduce physiological and emotional morbidity and improve quality of life. Neuraxial blocks not only reduce the incidence of venous thrombosis, pulmonary embolism, cardiac complications, bleeding transfusion requirements and respiratory depressions but also provide effective postoperative analgesia. One of the methods of providing postoperative is to prolong the duration of intrathecally administered bupivacaine by using additives such as opioids such as midazolam, clonidine and ketamine. Intrathecal administration of midazolam induces antinociceptive effects in humans. The present study was undertaken to evaluate the additive analgesic effects of intrathecal midazolam in combination with bupivacaine in lower limb surgeries in a tertiary care hospital and to compare the results with the use of bupivacaine alone. The aim of this study was to observe and compare the quality of spinal anaesthesia and occurrence of side effects in thirty cases administered with bupivacaine and thirty cases administered with bupivacaine-midazolam combination. Methods: Sixty cases admitted for lower limb surgery were divided into equal groups I and II. Cases in group I received intrathecal bupivacaine while those in group II received intrathecal combination of bupivacaine and midazolam. Data regarding quality of anesthesia and side effects were recorded and compared. Results: There was a significantly higher duration of a pain-free period in cases administered with intrathecal combination of bupivacaine and midazolam. Conclusions: Addition of preservative free midazolam to 0.5% hyperbaric bupivacaine for subarachnoid block prolongs the duration of effective analgesia as compared to bupivacaine alone. The utilization of intrathecal midazolam also decreases the incidence of postoperative nausea-vomiting.